Examining the Impact of Miles & Snow's Business Strategy, Operational Efficiency, and Logistics Efficiency on Company Performance - Habibie, Taufiq Chandra Adimanta; Anisah, Hastin Umi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
The COVID-19 pandemic has caused major disruptions to the global economy, resulting in significant economic contraction and rising unemployment across many nations. This study explores the influence of Miles & Snow’s business strategy typology, alongside operational and logistics efficiency, on the financial performance of companies. This study employs a quantitative approach, with data collected from 45 respondents serving as managers and supervisors at Midea-Toshiba Electronics during the 2021-2024 period. Purposive sampling method was used to ensure that only functionally relevant participants were involved. The survey instrument was distributed online and analyzed using the Partial Least Squares (PLS) approach. Hypothesis testing results show that all three independent variables significantly influence company performance. Logistics efficiency demonstrates the strongest influence (β = 0.481; f² = 0.524), followed by operational efficiency (β = 0.296; f² = 0.433), and business strategy (β = 0.253; f² = 0.884). These findings emphasize that optimal company performance is determined not only by appropriate strategic direction, but also by operational effectiveness and supply chain efficiency. This study provides contextual contribution in applying Miles & Snow's strategy typology in the regional industrial sector and serves as a foundation for formulating data-based company performance improvement policies.